Raw material inventory control system for small companies: Sistem pengendalian persediaan bahan baku untuk perusahaan kecil - L. Happy Amira; Yuanis Yuanis; Sarjono Sarjono (Universitas Muhammadiyah Sidoarjo, 2019)
For companies, the problem of managing raw material supplies is very important. This requires adequate management techniques. This means that all company operations are carried out in accordance with established plans and procedures and always lead to the goals to be achieved by Integration. Implementation of raw material management requires intensive inspection, so companies need to carry out internal audits. Internal audit inspection must be carried out objectively and independently in carrying out its duties. Problems that arise in this study (1) How is the application of internal audit raw material inventory management at UD company. Makmur Semanding? (2) Whether internal audit raw material inventory management can improve the efficiency and effectiveness of UD company operations. Makmur Semanding? The purpose of this study is (1) to describe how the implementation of internal audit management of raw materials at UD company. Prosperous Semanding. (2) To illustrate whether the internal audit of raw material inventory management can improve the efficiency and effectiveness of UD company operations. Prosperous Semanding. For the purposes of analysis and discussion, the authors use analysis techniques as flow chart analysis tools are used to determine the supply of raw materials to company management. Based on the provisions of Article 3 is the determination of the category value, then by calculating the score of raw material inventory management UD company sales revenue. Makmur Semanding is included in the sufficient category, because the total score is 91, this score is in the range of scores between 62-92.